Black Brant Branta bernicla nigricans grit acquisition at Humboldt Bay, California, USA - Spragens, Kyle A.; Bjerre, Emily R.; Black, Jeffrey M. (Wildfowl, 2013)
The Black Brant Branta bernicla nigricans is a seagrass-obligate goose, strongly tied to theÂ estuaries of the Pacific Flyway coast of North America. Black Brant are unique in thatÂ they remain reliant on their traditional food resource, in contrast to other Brent GooseÂ populations that now readily switch to feed on agricultural land during migration andÂ in winter. While Black Brant use of coastal estuaries within the Pacific Flyway isÂ determined mainly by the presence of Common Eelgrass Zostera marina, accessible gritÂ sites are a second, often overlooked, yet essential requirement that may be in partÂ responsible for stop-over duration within these coastal estuaries. This paperÂ synthesises existing literature and presents previously unpublished data from a seriesÂ of studies conducted at Humboldt Bay, California, describing the role and importanceÂ of grit sites to Black Brant. We found that the local environment influences gizzardÂ grit composition and, although evidence for grit selectivity by Brant makes itÂ challenging, it is possible to link a Brantâ€™s current gizzard contents to a previously usedÂ bay or grit site. The interval between successive sightings of ringed individualsÂ identified at the primary grit site varied (mean Â± s.d. = 8.6 Â± 9.6 days, range = 4.5â€“10.1Â days). We suggest that, during spring staging, individual geese must weigh trade-offs ofÂ time spent taking grit with time lost for other activities â€“ including foraging.